Epidemiological Dynamics and Public Health Challenges of Mpox in Southern Thailand - Ismail, Andi Almeira Zocha; Rahman, Siti Zulaikha; Anchana, Bamrungsap; Chantanee, Namuangruk; Bamrungsap, Pongkarn (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2024)
Mpox, a zoonotic viral disease, has emerged as a significant public health concern globally, especially since its spread beyond Central and West Africa in 2022. This study focuses on the epidemiological patterns of mpox in Southern Thailand, a region characterized by frequent human-wildlife interactions and cross-border activity. The findings reveal a high concentration of mpox cases in rural areas, with a prevalence rate of 15.4 per 100,000 population. The majority of cases occurred among males aged 25-40, highlighting a demographic trend linked to occupational and travel-related exposure. Transmission patterns indicate that close contact with infected individuals and wildlife are critical factors, with occupational exposure in rural areas posing significant risks. Public health interventions, such as isolation, hygiene promotion, and education, have been somewhat effective in urban settings but face challenges in rural areas due to limited healthcare access and low public awareness. The study emphasizes the need for targeted interventions, improved surveillance, and expanded vaccination efforts to mitigate the spread of mpox, particularly in regions with significant wildlife contact. Understanding these dynamics is essential for future outbreak control efforts in Southeast Asia and beyond.